Diachrony and diachronica: 40@40 - Bowern, Claire Louise; Smith, John Charles; Sneller, Betsy; Tamminga, Meredith; Gvozdanović, Jadranka; Goldsmith, John; Keydana, Götz; Blevins, Juliette (Diachronica, 2024)
Welcome to e-content platform of John Benjamins Publishing Company. Here you can find all of our electronic books and journals, for purchase and download or subscriber access.
Gesehen am 21.01.2026